(untitled) (Al-Qamar, 2026)
This study explores the Prophet Muhammad’s (ﷺ) use of the body, mosque, gifts, and letters as material means of da‘wah, with a focus on their ethical and communicative dimensions. Employing qualitative desk research and thematic analysis of authentic hadith and sirah sources, the study finds that material tools in da‘wah are effective in conveying messages, fostering interpersonal relationships, and facilitating moral persuasion within clear ethical boundaries, while also enabling the application of guidance in practice. The study concludes that adopting the prophetic model provides a relevant ethical framework for enhancing the effectiveness, credibility, and sustainability of contemporary da‘wah in pluralistic societies.